2018
DOI: 10.1039/c8ra09048c
|View full text |Cite
|
Sign up to set email alerts
|

Cu-catalyzed cross-coupling reactions of vinyl epoxide with organoboron compounds: access to homoallylic alcohols

Abstract: Copper-catalyzed cross-coupling reactions of vinyl epoxide with arylboronates to obtain aryl-substituted homoallylic alcohols are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…1 H NMR (400 MHz, Chloroform-d) δ 7.80–7.76 (m, 3H), 7.69 (s, 1H), 7.58 (dd, J = 8.7, 1.8 Hz, 1H), 7.47–7.40 (m, 2H), 6.66 (d, J = 15.9 Hz, 1H), 6.34 (dt, J = 15.8, 7.1 Hz, 1H), 3.80 (t, J = 6.3 Hz, 2H), 2.57–2.52 (m, 2H), 1.51 (s, 1H); 13 C­{ 1 H} NMR (101 MHz, Chloroform-d) δ 134.7, 133.6, 132.9, 132.8, 128.1, 127.9, 127.6, 126.8, 126.2, 125.8, 125.7, 123.4, 62.1, 36.5. The spectroscopic properties were consistent with the data available in the literature …”
Section: Methodssupporting
confidence: 90%
See 3 more Smart Citations
“…1 H NMR (400 MHz, Chloroform-d) δ 7.80–7.76 (m, 3H), 7.69 (s, 1H), 7.58 (dd, J = 8.7, 1.8 Hz, 1H), 7.47–7.40 (m, 2H), 6.66 (d, J = 15.9 Hz, 1H), 6.34 (dt, J = 15.8, 7.1 Hz, 1H), 3.80 (t, J = 6.3 Hz, 2H), 2.57–2.52 (m, 2H), 1.51 (s, 1H); 13 C­{ 1 H} NMR (101 MHz, Chloroform-d) δ 134.7, 133.6, 132.9, 132.8, 128.1, 127.9, 127.6, 126.8, 126.2, 125.8, 125.7, 123.4, 62.1, 36.5. The spectroscopic properties were consistent with the data available in the literature …”
Section: Methodssupporting
confidence: 90%
“…13 C and 19 F NMR spectra are fully decoupled by broad band proton decoupling. High Resolution Mass spectra were obtained from micro TOF-Q 134 High-resolution MS. Optical rotations were reported as follows: [α] 26 D (c g/100 mL, solvent). General Procedures A for The Remote Desaturation.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our first attempt to develop a synthetic route to alkene impurity 10 from methyl ( E )-4-(2,4,5-trifluorophenyl)­but-2-enoate ( 12 ) was to perform regio-isomerization of allylbenzene intermediate 12 to the regio-isomerized product 13 (Scheme ). Previous studies have indicated that bases, such as NH 3 , LiO t Bu, LiHMDS, K 2 CO 3 , , KF, KOH, and KO t Bu, , can promote the regio-isomerization of the allylbenzene derivative. Accordingly, the conversion of 12 to 13 in the presence of different bases (NaH, Et 3 N, NMM, and DBU) was monitored by NMR (see the Supporting Information, Table S1).…”
Section: Resultsmentioning
confidence: 99%